2020
DOI: 10.3389/fphar.2020.574441
|View full text |Cite
|
Sign up to set email alerts
|

L-Carnitine Mitigates Oxidative Stress and Disorganization of Cytoskeleton Intermediate Filaments in Cisplatin-Induced Hepato-Renal Toxicity in Rats

Abstract: Cisplatin (CP) is one of the most active medications in cancer treatment and has some adverse effects such as hepatotoxicity and nephrotoxicity. The present research was planned to determine the protective effects of L-carnitine (LC) against CP-induced hepatorenal oxidative stress in rats, via investigating of some serum biochemical and tissue oxidative/antioxidant parameters, histological alterations, and immunohistochemical expressions of two different intermediate filaments (IFs) proteins; vimentin (VIM) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 76 publications
(143 reference statements)
4
14
0
Order By: Relevance
“…L-carnitine an innate component of mammalian tissue synthesized from lysine and methionine essential amino acids. It is derived from dietary sources (75%) and endogenous biosynthesis (25%) mainly in the liver and kidney, is a necessary factor for the utilization of long-chain fatty acids to produce energy in mitochondria ( Elkomy et al, 2020 , Jin et al, 2019 , Sallam et al, 2020 ). It has been shown to function as an antioxidant that scavenges reactive oxygen species (ROS); so could prevent mitochondrial oxidative stress-induced by mitochondrial damage and apoptosis in different cell types, and also elicits stabilizing effect on damaged cell membranes ( Dokmeci et al, 2006 , Edres et al, 2018 , Ghonem et al, 2018 , Sallam et al, 2020 , Sarica et al, 2007 ).…”
Section: Introductionmentioning
confidence: 99%
“…L-carnitine an innate component of mammalian tissue synthesized from lysine and methionine essential amino acids. It is derived from dietary sources (75%) and endogenous biosynthesis (25%) mainly in the liver and kidney, is a necessary factor for the utilization of long-chain fatty acids to produce energy in mitochondria ( Elkomy et al, 2020 , Jin et al, 2019 , Sallam et al, 2020 ). It has been shown to function as an antioxidant that scavenges reactive oxygen species (ROS); so could prevent mitochondrial oxidative stress-induced by mitochondrial damage and apoptosis in different cell types, and also elicits stabilizing effect on damaged cell membranes ( Dokmeci et al, 2006 , Edres et al, 2018 , Ghonem et al, 2018 , Sallam et al, 2020 , Sarica et al, 2007 ).…”
Section: Introductionmentioning
confidence: 99%
“…[6,7] CIS induces the cytotoxic effect via association with the DNA by facilitating a covalent adduct between the platinum compound and purine bases, which triggers apoptosis and G2 cell cycle arrest. [10][11][12] Apart from its antitumor effect, CIS has numerous toxic and adverse effects, which influence the gastrointestinal, hematological, and neurological systems. However, CIS administration has been accompanied by nephrotoxicity, cardiotoxicity, hepatotoxicity, and ovarian toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…Clinical studies have shown, l -carnitine supplementation can enhance myocardial fat metabolism due to the increased demand for free fatty acids and their metabolites and thus creates a beneficial effect on myocardial function [ 31 , 32 ]. Besides, therapeutic potentials of l -carnitine have been investigated in many rat models, for instances, in tilmicosin-induced cardiotoxicity [ 33 ], and imatinib-induced cardiotoxicity [ 34 ].…”
Section: Discussionmentioning
confidence: 99%